2022
DOI: 10.31234/osf.io/mp84a
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

What is Meant by “Growth Mindset”? Current Theory, Measurement Practices, and Empirical Results Leave Much Open to Interpretation

Abstract: The past decade has seen a rising interest in the growth mindset—the belief that abilities are malleable. At the same time, there have been rising criticisms. Macnamara and Burgoyne claim that growth mindset interventions do not yield meaningful effect sizes; growth mindset proponents argue that they do, for specific populations and under specific conditions. We speculate that disagreements stem from core questions for which this field has not yet answered or reached a consensus: What is meant by growth mindse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 98 publications
0
7
0
Order By: Relevance
“…Notably, prior work has consistently demonstrated that these nuances are empirically distinguishable-even among young children-and, perhaps surprisingly, sometimes only weakly related to one another (e.g., [12,48,49]). In light of these considerations, and consistent with recent calls for more multifaceted measures of mindsets that can better capture the complexity of people's reasoning about ability [50], we assessed two perspectives on changeability that we perceived to be conceptually central to mindsets: children's beliefs about the extent to which ability is (a) stable across time and (b) responsive to intervention. To make the questions as concrete and easy to follow as possible, we introduced participants to a drawing of a child character, provided the character with a name, and said that the character currently was either good or not good in one of the three domains.…”
Section: Our Approach To Designing a Measure Of Young Children's Mind...mentioning
confidence: 98%
See 1 more Smart Citation
“…Notably, prior work has consistently demonstrated that these nuances are empirically distinguishable-even among young children-and, perhaps surprisingly, sometimes only weakly related to one another (e.g., [12,48,49]). In light of these considerations, and consistent with recent calls for more multifaceted measures of mindsets that can better capture the complexity of people's reasoning about ability [50], we assessed two perspectives on changeability that we perceived to be conceptually central to mindsets: children's beliefs about the extent to which ability is (a) stable across time and (b) responsive to intervention. To make the questions as concrete and easy to follow as possible, we introduced participants to a drawing of a child character, provided the character with a name, and said that the character currently was either good or not good in one of the three domains.…”
Section: Our Approach To Designing a Measure Of Young Children's Mind...mentioning
confidence: 98%
“…Prior work has shown that children's judgments about the changeability of intellectual ability depend on its initial level, with children viewing high ability as less changeable than low ability (e.g., [51,52]). Considering these findings, we deemed it important to vary the initial ability level of the characters in the vignettes (see also [50]). Doing so also allowed us to make the content of the questions even more concrete, which is desirable given that the scale is intended for young children.…”
Section: Our Approach To Designing a Measure Of Young Children's Mind...mentioning
confidence: 99%
“…The following sections are devoted to a brief review of the conceptual underpinnings of the relationships between teachers' mindset and the three types of outcomes (teacher outcomes, instructional practices, student outcomes) and prior research on each of the respective associations. The selection of outcomes for our meta-analysis was guided by (a) conceptual ties between mindset and specific variables previously established in mindset research (e.g., variables that belong to the "meaning system" that mindsets create, such as goals, ; see also Yan & Schuetze, 2023), (b) the relevance of certain outcomes (i.e., student achievement) to research on teacher characteristics in general, further substantiated by recent increases in interest in teacher mindset and its role in promoting student achievement (e.g., Yeager et al, 2022), and (c) the consideration of instructional practices as critical outcomes on their own, also potentially serving as (behavioral) factors of transmission from teacher mindset to student outcomes (see also Blackwell et al, 2007;Lam & Zhou, 2020;Yan & Schuetze, 2023, for the importance of studying behaviors in mindset research).…”
Section: Relationships Between Teachers' Mindset and The Considered O...mentioning
confidence: 99%
“…In the present meta-analysis, we focused on three moderators related to the measurement of mindsets, considering that in any study or meta-analysis, the way constructs are translated into measures can largely affect the findings. Furthermore, measurement aspects might be particularly important to address in the mindset domain, due to several unresolved issues surrounding the assessment and definition of the construct (e.g., Limeri et al, 2020;Lüftenegger & Chen, 2017;Yan & Schuetze, 2023).…”
Section: Potential Moderatorsmentioning
confidence: 99%
See 1 more Smart Citation